2014
DOI: 10.1155/2014/872139
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizic Acid in the Treatment of Liver Diseases: Literature Review

Abstract: Glycyrrhizic acid (GA) is a triterpene glycoside found in the roots of licorice plants (Glycyrrhiza glabra). GA is the most important active ingredient in the licorice root, and possesses a wide range of pharmacological and biological activities. GA coupled with glycyrrhetinic acid and 18-beta-glycyrrhetic acid was developed in China or Japan as an anti-inflammatory, antiviral, and antiallergic drug for liver disease. This review summarizes the current biological activities of GA and its medical applications i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
173
0
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(189 citation statements)
references
References 95 publications
1
173
0
15
Order By: Relevance
“…Glycyrrhizin (GZ; Figure 1a) is the main active component in licorice and it is reported that its content is in the range of 2-15% (w/w) depending on the plant species, geographic and climatic conditions (Fenwick, 1990). GZ exerts multiple biochemical and pharmacological activities, including antiallergic, antiviral, immunoregulatory and anti-inflammatory activities (Eisenbrand, 2006;Fu et al, 2014;Li et al, 2014a;Ma et al, 2013;Nagai et al, 1992). In addition, GZ is thought to be responsible for the characteristic sweetness and taste typically associated with licorice products (Seki et al, 2008), and thus has been used widely as a sweetening and flavoring agent in substances such as food and tobacco (Isbrucker & Burdock, 2006;Olukoga & Donaldson, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Glycyrrhizin (GZ; Figure 1a) is the main active component in licorice and it is reported that its content is in the range of 2-15% (w/w) depending on the plant species, geographic and climatic conditions (Fenwick, 1990). GZ exerts multiple biochemical and pharmacological activities, including antiallergic, antiviral, immunoregulatory and anti-inflammatory activities (Eisenbrand, 2006;Fu et al, 2014;Li et al, 2014a;Ma et al, 2013;Nagai et al, 1992). In addition, GZ is thought to be responsible for the characteristic sweetness and taste typically associated with licorice products (Seki et al, 2008), and thus has been used widely as a sweetening and flavoring agent in substances such as food and tobacco (Isbrucker & Burdock, 2006;Olukoga & Donaldson, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Glycyrrhizin, a triterpene glycoside from root of Glycyrrhiza glabra, has positive effects on inhibition of hepatic apoptosis and necrosis by suppression of TNF-α and caspase-3, an important cytokine, which is a key mediator of hepatic apoptosis and necrosis in LPS/D-GaAlN-induced liver failure [11] and downregulation of matrix metalloproteinase-9 in lipopolysaccharide/ D-galactosamine-induced liver injury [12].…”
Section: Therapeutic Potentials and Traditional Usesmentioning
confidence: 99%
“…Stronger neominophagen C (SNMC, Minophagen Pharmaceutical, Tokyo, Japan), was first reported by Yamamoto et al in 1958, and has now been used in the treatment of chronic liver disease for more than 50 years. SNMC is a compound GA tablet that includes GA (2 mg) together with glycine acid (20 mg) and L-cysteine hydrochloride (1 mg) [31] . In 1977, Arase et al [32] confirmed its ability to reduced aminotransferase levels in patients with histologically-documented chronic hepatitis in a doubleblind randomized controlled trial using a dose of 40 mL daily for a month.…”
Section: Glycyrrhizin (Glycyrrhizic Acid) Stronger Neo-minophagen Cmentioning
confidence: 99%